In action: how polymer-based materials are the quiet but powerful drivers of progress - Mohd Zaki, Syazwani (Institute of Materials, Minerals and Mining (IOM3), UK, 2025)
Every technological leap in human history has been underpinned by a corresponding leap in materials. The Stone Age, the Bronze Age and the Iron Age were all defined by the substances people mastered. Today, we are living in what could easily be called the ‘Polymer Age’.